Sports Teaching, Traditional Games, and Understanding in Physical Education: A Tale of Two Stories - Martínez-Santos, Raúl; Founaud, María Pilar; Aracama, Astrid; Oiarbide, Asier (Frontiers in Psychology, 2020)
Unlike Dickens’s novel, this is not a tale of light and darkness, order and chaos, good and evil… It is, though, a story worth to be told about two standpoints about games and sports, teaching and research, physical education simply put, that have pursued similar interests on parallel tracks for too long, despite their apparent closeness and expected shared cultural grounds. The objective of this conceptual analysis is to try and reconcile two perspectives, namely motor praxeology and teaching games for understanding (TGfU), born in the last third of the XX century in France and England with the intention to rethink the foundations of physical education (PE) and sports teaching. Pierre Parlebas, from the French side of the English Channel, claimed in 1967 that sports make part of PE, that team sports must be considered from a specific, sociomotor point of view, and that motor conducts (i.e. the significative organization of motor behaviour), not sports techniques, are the corner-stone of PE and sports coaching. In the early 1980s, from the English side of La Manche, Almond, Thorpe, and Bunker made a plea for a shift in the way to teach games (sporting collective duels mostly), deeply concerned by the negative impact of the traditional technics-centred approach on motivation, competence and attained level of the least able in school situations. Our conclusion is that TGfU, or game-based approaches to sports coaching and teaching, can take great advantage of the motor-praxeological rationale for three reasons: firstly, because concepts like understanding, game sense and action principles are operatively, semiotically linked to the reality of the playing process; secondly, because the inner structures of the games that constrain players and guide their motor conducts, permit to integrate games in the general system of sporting games, no matter their level of institutionalisation; finally, because the intervention practice is better thought of and more systematically developed upon the operational concepts of internal logic and expected practical effects of game playing. This time, Paris could be the place to go to in search of solutions, not the city to run away from in hope of consolation.